Black Soldier Fly Maggot Drying Technology to Enhance Livestock Feed Production in Bekiung Village, Kuala Subdistrict, Langkat District - Noer, Zikri; Nainggolan, Irwana; Azhari; Banurea, Rahmadhani; MN, Nasruddin (Talenta Publisher, 2023)
The Tani Melati Group located in Desa Bekiung, Kecamatan Kuala, Kabupaten Langkat is a farmer group that pioneered the cultivation of Black Soldier Fly (BSF) maggot larvae, currently capable of producing about 10 kg of maggot larvae per week. The existence of this farmer group is very helpful for the community and the local government in managing the existing organic waste. Production of maggot larvae in this village is improving the quality of feed, but is hampered by the need for a roasting oven for drying BSF maggots. This service aims to assist partners in improving the quality of BSF Maggot to be used as animal feed using the BSF Maggot Roast oven drying machine and to socialize the post-harvest processing of BSF Maggot feed into freshwater floating fish. The socialization activity of making floating fish feed with Maggot BSF as the main protein source was carried out by comparing the protein sources of fish scales with maggots. The conclusion of this service activity is that there is an additional tool for managing BSF Maggot as animal feed in the form of BSF Maggot Roast Drying technology which has great potential in improving the quality, quantity, and expiration of the BSF Maggot which is getting longer. In addition, partners also gain new knowledge in the form of how to manage BSF maggots into floating fish feed that can be used in freshwater fish farming. This service output program includes fish feed training services, procurement of drying technology using a roasting oven, activity videos, and scientific articles.